ECONOMIC LOSSES FROM THE DESTRUCTION OF WATER SUPPLY SYSTEMS: AN ASSESSMENT FOR HOUSEHOLDS, THE AGRICULTURAL SECTOR, AND INDUSTRY IN UKRAINE - Kovtun, Oksana; Palahusynets, Rostyslav (Public Management and Policy, 2025)
The article examines the economic losses resulting from the destruction of water supply infrastructure in Ukraine, taking into account the impact on households as well as the agricultural and industrial sectors. It is established that the war has caused significant damage to the natural environment, including ecosystems and water resources, which has led to increasing economic and social risks. It is emphasized that the scale of water infrastructure destruction directly affects the livelihood of the population and the functioning of production processes, underscoring the importance of restoring water supply systems in the context of sustainable development. It is noted that as of September 2025, only 68% of Ukraine’s population had access to centralized water supply, while in rural areas this figure amounted to just 26%, resulting in critical inequality in access to water. The study identifies that the low level of access to safe water increases household expenditures on alternative water sources and limits the production capacities of the agricultural and industrial sectors. It is highlighted that military actions have substantially intensified the degradation of water pipelines and engineering facilities, affecting approximately 39.7 thousand km of water supply systems with total economic losses estimated at USD 4.6 billion. The article presents regional disparities in losses that correlate with the intensity of hostilities: the largest damages occurred in Luhansk, Kharkiv, and Zaporizhzhia regions, confirming the need for territorially differentiated investment. It is determined that the modernization of irrigation and drainage systems is a priority of state policy to ensure agricultural productivity and reduce pressure on ecosystems. It is stressed that the combined impact of destruction has caused significant economic losses in households and in the agricultural and industrial sectors, while further exacerbating disparities in access to water resources. The study concludes that an integrated approach to modernizing water supply systems, including infrastructure restoration and the use of modern technologies, is a crucial factor for ensuring socio-economic stability in the post-war recovery period.